A history of English reflexive pronouns : person, self, and interpretability - Gelderen, Elly van (Linguistik aktuell ;, 2000)
This book brings together a number of seemingly distinct phenomena in the history of English: the introduction of special reflexive pronouns (e.g. myself), the loss of verbal agreement and pro-drop, and the disappearance of morphological Case. It provides vast numbers of examples from Old and Middle English texts showing a person split between first, second, and third person pronouns. Extending an analysis by Reinhart & Reuland, the author argues that the 'strength' of certain pronominal features (Case, person, number) differs cross-linguistically and that parametric variation accounts for the.